Simultaneous manipulation of line-gap and point-gap topologies in non-hermitian lattices - Liu, Dongjue (2023)
Non-Hermiticity may significantly influence the topology of a photonic/electronic lattice, giving rise to point gaps, which have attracted much attention in recent years. While the influences of the point-gap topology on the bulk-boundary correspondence for the line gap have been widely studied, the topological lattice that simultaneously processes the line-gap and point-gap topological transitions has not been reported. Here, a strategy to simultaneously manipulate the line-gap and point-gap topologies in non-Hermitian lattices is proposed. By introducing the asymmetric intercell coupling, the line-gap topological transition process is demonstrated. By further considering the nonreciprocal coupling between the nearest neighboring unit cells, the point-gap and line-gap topological transitions can be simultaneously realized. Finally, the influence of the next nearest coupling on non-Hermitian line-gap and point-gap topologies is also discussed.